The Role Of Constitutional Rulers: A Malaysian Perspective For The Laity - Azlan Shah, Y.A.M. Raja Tun (Journal of Malaysian and Comparative Law, 1982)
The Role Of Constitutional Rulers: A Malaysian Perspective For The Laity